Redescription of Leptogyra bujnitzkii (Gorbunov, 1946) comb. nov., the first representative of the gastropod subclass Neomphaliones from the high Arctic - Krol, Ekaterina N.; Nekhaev, Ivan O. (Zootaxa, 2020)
Ganesa bujnitzkii Gorbunov, 1946 was described from the bathyal of the Arctic Ocean north to the Laptev Sea based on only two specimens, which were the only representatives of this species mentioned by Gorbunov (1946b). Galkin (1955) noted that the shell sculpture of Ganesa bujnitzkii is similar to that of Cyclostrema valvatiodes (Jeffreys, 1883), and that the radula of the G. bujnitzkii differs from other species of the genus Ganesa Jeffreys, 1883 and members of the family Trochidae. Later, based on the original description, Warén (1993) proposed that the species may belong to the genus Skenea; however, he did not examine the type specimen. This opinion was reiterated by Kantor & Sysoev (2006).